2001
DOI: 10.1128/jcm.39.8.2928-2932.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of COBAS AMPLICOR (Roche): Accuracy in Detection of Chlamydia trachomatis and Neisseria gonorrhoeae by Coamplification of Endocervical Specimens

Abstract: We evaluated further the accuracy of the COBAS AMPLICOR (Roche) (CA) PCR-based system in detection of Chlamydia trachomatis and Neisseria gonorrhoeae in endocervical specimens. Endocervical specimens collected for any indication for testing for C. trachomatis and N. gonorrhoeae among a university hospital health system population were included. Testing for C. trachomatis was done by two PCR methods, CA and manual microwell AMPLICOR (Roche) (MWA), and by culture; testing for N. gonorrhoeae was done by CA and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…Previous studies have reported similar specificities, with corresponding PPVs of more than 80% (4,10,13,14). Although these specificities are high, there is controversy in the literature with respect to the methods used to calculate them, particularly in regards to the use of discrepant analysis (7,8).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies have reported similar specificities, with corresponding PPVs of more than 80% (4,10,13,14). Although these specificities are high, there is controversy in the literature with respect to the methods used to calculate them, particularly in regards to the use of discrepant analysis (7,8).…”
Section: Discussionsupporting
confidence: 53%
“…Studies on the utility of this test in diagnosing infection with N. gonorrhoeae have demonstrated sensitivities ranging from 92.4 to 100% for endocervical or urethral swabs and from 42.3 to 94.1% for urine specimens, while specificity has been high (95.9 to 99.9%) for all specimens (4,5,10,13,14,(20)(21)(22). The majority of these studies were performed in populations with a high prevalence (4.4 to 20.1%) of infection, resulting in positive predictive values (PPV) greater than 80%.…”
mentioning
confidence: 99%
“…The specificity measured by using the interpretation defined for this study resulted in PCR specificities of 99.3 and 99.0% for C. trachomatis and N. gonorrhoeae, respectively. These values are well within the range reported for this assay (12,18,22,29,30).…”
Section: Discussionsupporting
confidence: 75%
“…Although these assays have demonstrated excellent sensitivities and specificities in clinical trials (6,28,29,30), they require extreme technical precision in order to achieve maximum performance (18,22,28). With the assays available at present, this translates into labor-intensive diagnostic methods, often with low-throughput capacity (2,3,16).…”
mentioning
confidence: 99%
“…Along with the rapid generation of results, C. trachomatis-specific (20,25,32) and N. gonorrhoeaespecific (20,22,25) nucleic acid hybridization assays provide analytical sensitivities equivalent to that of culture. The commercial availability of nucleic acid amplification tests (NAATs) has greatly enhanced the detection of both of these agents (1,7,11,15,29,30) in genital swab specimens submitted to clinical laboratories.…”
mentioning
confidence: 99%